Annual Plan 2005-2006 West Bengal - Planning Commission (Planning Commission, 2005)
There have been remarkable achievements in the production of food grains in the State of West Bengal in recent years. This has been the result of progressive and systematic planning and implementation of various crop development programmes/schemes (State Plan, Central Sector and Centrally Sponsored Schemes) launched by the State Govt., the dedication of our people engaged in agriculture, involvement of “Panchayati Raj System” and application of modern crop production technology in the field.
Development and Planning Department, Government of West Bengal